PENGARUH DIGITAL MARKETING TERHADAP PERKEMBANGAN UMKM - Nugroho, Akbar Adi; Ahmadi , Mirzam arqy (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research examines the influence of digital marketing implementation on the development of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Amid rapid digital transformation, MSMEs face both challenges and opportunities in adopting digital marketing strategies to enhance their competitiveness. Using qualitative research methods with a library research approach, this study analyzes various literature and documents related to digital marketing implementation in the MSME sector. The results show that digital marketing adoption has a significant positive impact on MSME development, with an average revenue increase of 80% in the first two years of implementation. However, the success of this implementation is influenced by various factors, including digital literacy, infrastructure, and financial capabilities of MSMEs. This research also identifies the importance of an integrated approach in digital marketing implementation, which includes digital competency development, infrastructure strengthening, and ecosystem collaboration. The research findings provide theoretical and practical contributions to the development of effective digital marketing strategies for MSMEs, as well as serve as a reference for stakeholders in formulating policies and support programs for MSME digitalization. Penelitian ini mengkaji pengaruh implementasi digital marketing terhadap perkembangan Usaha Mikro, Kecil, dan Menengah (UMKM) di era digital. Di tengah transformasi digital yang semakin pesat, UMKM menghadapi tantangan sekaligus peluang dalam mengadopsi strategi digital marketing untuk meningkatkan daya saing mereka. Menggunakan metode penelitian kualitatif dengan pendekatan studi kepustakaan, penelitian ini menganalisis berbagai literatur dan dokumen terkait implementasi digital marketing pada sektor UMKM. Hasil penelitian menunjukkan bahwa adopsi digital marketing memberikan dampak positif signifikan terhadap perkembangan UMKM, dengan peningkatan omzet rata-rata sebesar 80% dalam dua tahun pertama implementasi. Namun, keberhasilan implementasi ini dipengaruhi oleh berbagai faktor, termasuk literasi digital, infrastruktur, dan kapabilitas finansial UMKM. Penelitian ini juga mengidentifikasi pentingnya pendekatan terintegrasi dalam implementasi digital marketing, yang mencakup pengembangan kompetensi digital, penguatan infrastruktur, dan kolaborasi ekosistem. Temuan penelitian memberikan kontribusi teoretis dan praktis dalam pengembangan strategi digital marketing yang efektif untuk UMKM, serta menjadi acuan bagi pemangku kepentingan dalam merumuskan kebijakan dan program pendukung digitalisasi UMKM.